Addicted to the moon: vocal output and diel pattern of vocal activity in two Neotropical nightjars is related to moon phase. Issue 1 (2nd January 2022) - Pérez-Granados, Cristian; Schuchmann, Karl-L.; Marques, Marinez I.
Abstract : The moon phase affects the ecology and vocal activity of nightjars (Caprimulgidae). However, some studies have found contradictory results regarding the impact of the moon phase on the vocal activity of nightjars. To increase our knowledge on this topic, we monitored the vocal behavior of two Neotropical nigthjars, the Little nightjar ( Setopagis parvula ) and the Common pauraque ( Nyctidromus albicollis ), over 5 lunar cycles in the Brazilian Pantanal. We tested the relationships between the moon phase and daily vocal output (number of calls uttered) and the proportions of calling activity at dusk, midnight, and dawn. Our results suggest that moonlight stimulated the vocal output of both species, since it was between 6 and 8 times higher during full moon nights than during new moon nights. Likewise, the proportion of calling activity at midnight was significantly higher during full moon nights. In contrast, the proportion of calling activity of both species was higher at dawn during new moon nights than under the full moon. The calling activity of the Common pauraque was also higher at dusk during new moon nights. These findings might be partly related to the much lower vocal output at midnight during full moon nights and therefore higher proportions of vocal activity at dusk and at dawn under new moon scenarios. This is the first study comparing the vocal behavior of two Neotropical nightjars over different moon phases and shows that the impact of moonlight may differ between species and at a daily scale when analyzing the periods with the highest and lowest illumination. The consequences of the increase in vocal output under moonlight are unknown and should be assessed.